Hyperthyroidism: A rare cause of pulmonary embolism: Report of two cases - Grine, Sonia (Medknow Publications & Media Pvt Ltd, 2013)
Several disorders of coagulation and fibrinolysis have been widely reported in patients with hyperthyroidism. Most reports have focused on only the venous thromboembolism risk, and few of them have studied specifically the association between hyperthyroidism and pulmonary embolism (PE). We report two cases of Graves’ disease complicated by PE. The first patient is a 32 year-old man, and the second patient is a 23-year-old female. PE was suspected on the basis of pulmonary hypertension in patient one, and clinical presentation in the other patient. The first patient had also right heart failure. PE was confirmed in both patients by a lung perfusion-ventilation scan test. Thrombophilia screen revealed normal findings in the first patient and an elevation in coagulation factor VIII in the second one. Both patients received heparin, followed by oral anticoagulant therapy. In addition, they were treated with radioactive iodine resulting in partial recovery from hyperthyroidismforpatient oneand clinical euthyroidism for patient two. The former died of acute heart failure secondary to a chest infection, while the later was lost to follow-up. In conclusion, hyperthyroidism is associated with increased risk of venous thromboembolism, including PE. Potential mechanisms involved in this association include endothelial dysfunction, decreased fibrinolytic activity, and increased coagulation factors levels. Thyroid evaluation is recommended in patients with unprovoked venous thromboembolic events. Conversely, the diagnosis of venous thromboembolism should be considered in patients with hyperthyroidism, particularly if additional prothrombotic risk factors are present.